Adherence to iron/folic acid supplementation and associated factors among pregnant women attending governmental health center in Yeka Sub City, Addis Ababa, Ethiopia - Birhanu Tadesse Urgessa; Ziyad Ahmed Abdo (Wolters Kluwer Medknow Publications, 2020)
CONTEXT: Iron-folic acid deficiency is the leading nutritional deficiency globally, affecting the lives of >2 billion people, accounting over 30% of the world's population. Provision of iron-folic acid supplement to all pregnant women, is among the very critical interventions to reduce the burden of anemia. Even though the service is free in Ethiopia, the prevalence of anemia is slowly increased in the country. AIM: The aim is to assess adherence to iron-folic acid supplementation and associated factors among pregnant women attending governmental health center in Yeka sub city, Addis Ababa, Ethiopia, from November 1 to 30, 2019. METHODOLOGY: An institutional-based quantitative cross-sectional study was used to conduct the study. Systematic sampling system was used to select 408 study populations. Data were collected through interview using structured questionnaire. Bivariate and multivariable logistic regressions were employed to identify the predictor variables. Statistical significance was considered at P < 0.05 with adjusted odds ratio (AOR) calculated at 95% confidence interval (CI). RESULTS: A total of 408 pregnant women attending anti-natal care (ANC) were participated in this study, with response rate of 100%. The overall adherence rate was found to be 71.3%. Women whose family income >1500 Ethiopian Birr (ETB) (AOR [95% of CI]) = 3.77 (0.58-24.38)], having secondary or higher educational level (AOR [95% of CI]) = 1.48 (0.90-2.43), having history abortion (AOR [95% of CI] = 6.99 (1.11-44.19), starting ANC visit in first trimester (AOR [95% of CI] = 3.0 (0.24-37.18) were significantly associated with iron-folic acid supplementation. CONCLUSION: According to this study, adherence to iron-folic acid supplementation was relatively high. Empowering women in economy and education are very important. Proper counseling and health promotion about iron-folic acid supplementation, promoting the benefits of early and frequent ANC visit are very important to increase adhere to iron-folic acid supplementation.